COMPARISON OF WORLD HEALTH ORGANIZATION TREATMENT FOR ACUTE WATERY DIARRHEA IN CHILDREN WITH AND WITHOUT SACCHROMYCES BOULARDII IN TERMS OF MEAN DURATION OF DIARRHEA - Raza, Ali; Zahid, Muhammad; Qadir, Ehsan; Malik, Nazir Ahmed; Aslam, Sohail; Siddique, Kashif (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare World Health Organization treatment for acute watery diarrhea in children with and without probiotic Saccharomyces boulardii in terms of mean duration of diarrhea.Study Design: Comparative cross sectional study.Place and Duration of Study: Combined Military Hospital Tarbela, Pakistan, from Jan 2019 to Jul 2019.Methodology: Eighty four children were enrolled in this study using inclusion and exclusion criteria. Two groups were made. Group A was treated with oral Zinc (10mg for 6 months old for 14 days); low osmolarity Oral rehydration salt by 5 ml/kg per hour and continuation of nutritious feeding. Group B was treated with 250mg twice daily Sacchromyces boulardii along with oral Zinc (10mg for 6 months old for 14 days); low osmolarity Oral rehydration salt by 5 ml/kg per hour and continuation of nutritious feeding. Assessment included anthropometric measurements, hydration status, daily frequency and consistency of stools. Baseline investigations were sent to Combined Military Hospital, Tarbela Laboratory. Data was recorded on a specially designed proforma.Results: Duration of diarrhea was significantly lower in children who were given Saccharomyces boulardii with Zinc as compared to children who were given Zinc alone. i.e., group-A (Zinc): 53.31 hrs vs. group-B (Zinc+ Saccharomyces boulardii): 36.37 hrs, p